An Analysis of Classroom Interaction in International Class of Biology Department at Universitas Negeri Padang - Meutia Herza Putri; Ratmanida Ratmanida (Journal of English Language Teaching, 2022)
Classroom interaction is defined as an interaction between the teacher and learners, and amongst the learners in the classroom. Those interactions consequently lead to students’ attitudes whether it is positive or negative including in an International Class, especially in Biology Department. The research aims to find out how classroom interaction takes place between lecturer-students (L-S), students-lecturer (S-L), and student-student (S-S) and students’ attitudes towards the classroom interaction in International Class of Biology Department at Universitas Negeri Padang. This is a descriptive qualitative research conducted in the International class of Biology Department. The instruments of this research were observation, adopted questionnaire, and interview. The data analysis was analysed by categorizing each category of the patterns from FIACS. The participants of this research consisted of 41 students and 2 lecturers. From the five-meeting observation, the finding of the research revealed that dominant category of each pattern; explaining for L-S pattern, response for S-L pattern, and questioning for S-S. Those dominant categories were influenced by group discussion method that used in the teaching and learning process. In addition, students showed the positive attitudes towards interaction in the classroom, in which they had a passion and aspiration to maintain their ideas or thoughts independence.